(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Karur district is located in banks of amaravathi and kaveri rivers ,it is well known for its handloom textiles ,blanket exports,dyeing industries and netting industries.The ground water resources are well polluted due to the untreated effluent discharges of above mentioned industries.We have analysed the physio-chemical parameters of samples from 25 various locations in January and February month at northern part of karur district.(i.e.,pH,Turbidity,Electrical Conductivity,TDS,Hardness,etc.,) and interpulated the results with statistical approach,correlation and WQI.While interpolating the results with WQI we found that 12% of samples has a very poor status(75.7068) and 4% is unfit for drinking(157.124). 98% of samples is beyond 500mg/l while calculating TDS(highest range 5800mg/l at Noyyal.EC,pH are within the permissible limits.We can observe a drastical hike of results exceeding the permissible limit of Indian standards,WHO limits.We found a peak value of chlorides(2813mg/l)while testing Noyyal sample.Correlation gives positive value while correlating alkalinity with other parameters,this shows a direct proportionality of alkalinity with other parameters.For controlling these pollution and improving the ground water quality we must ensure of not mixing oils,cleaning chemicals,untreated effluents from industries into ground water.Air sparging and stripping,GAC filters,RO methods can be used for treating contaminated ground water.